The Mediating Effects of Knowledge Sharing: The Causal Relationship of Transformational Leadership and Organizational Culture with Innovative Work Behaviors: A Case Study of Airfreight Organizations in Thailand - Jangsiriwattana, Thamarat; Chaemlek, Adunyarat; Pojsupap, Thantip (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024, 2024)
This quantitative research aims to investigate the relationship between transformational leadership and organisational culture with innovative work behaviours. The mediating role of knowledge sharing is examined. Data were collected from 396 participants who work in 21 logistics firms that are members of the Thai Airfreight Forwarders Association. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results reveal that transformational leadership and organisational culture significantly affect innovative work behaviors in organisations. Furthermore, knowledge sharing amongst colleagues mediates such relationships. These findings add to the study of innovative work in the logistics industry. In addition, this study benefits HR in logistics firms in Thailand to focus on knowledge sharing to enhance innovative work behaviours. Implications are discussed in two folds, namely, theoretical and practical implications. Keywords:   Transformational Leadership, Organisational Culture, Knowledge Sharing, Innovative Work Behaviours, Airfrieght Organizations